Quality of life of the institutionalized elderly: Integrative review (International Seven Journal of Health Research, 2023)
More and more people are living longer lives, due to significant improvements in living conditions, infrastructure, technology and health, and this is causing enormous concern on the part of the public authorities, especially with regard to healthy ageing and quality of life. It is known that elderly people who are institutionalized have greater weaknesses in their health. Complaints about their state of health become greater when they live in philanthropic institutions. The general aim of this study was to investigate the quality of life of institutionalized elderly people through a literature review. This was an integrative literature review, in which data was collected after previous research in databases between April and May 2023. The absence of factors such as autonomy, intimacy and independence within ILPIs are considered to be influential factors in weakening the institutionalized elderly, especially when they are abandoned by both society and their family members. In addition, factors such as the low level of education, which is very common in ILPIs, contribute to the emergence of depressive episodes, since few elderly people have the ability to develop extracurricular activities. The literature selected to compose the results of this study shows that institutionalized elderly people do not have a good quality of life, largely due to family abandonment and the limitations of ILPIs, both in terms of activities and human resources.